Data underpinning "Soil seal development under simulated rainfall: structural, physical and hydrological dynamics" - Simmons, Robert W.; Armenise, Elena (Cranfield University, 2018)
Data used in the linked publication
Keywords: soil structural seal'; 'seal/crust thickness quantification'; 'X-ray computed tomography (CT)'; 'Agricultural Hydrology (Drainage; Flooding; Irrigation; Quality; etc.)'; 'Agricultural Land Management'